1994
DOI: 10.3109/00952999409106780
|View full text |Cite
|
Sign up to set email alerts
|

Children of Substance Abusers: The Life Experiences of Children of Opiate Addicts in Methadone Maintenance

Abstract: We interviewed 70 substance abusers in methadone maintenance treatment regarding the life experiences of their 188 children. Sixty-four percent of the mothers reported using psychoactive drugs during their pregnancies. Eighty percent of parents reported an arrest during the time the child was growing up, 34% reported receiving treatment for an emotional disorder, and 14% were hospitalized. Four percent of the parents reported that their children had been placed in adoptive care, 9% in foster care, and 1% had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 10 publications
2
44
0
Order By: Relevance
“…Kolar et al, 1994), and experimentation with or abuse of alcohol and drugs (Biederman et al, 2000;King et al, 2003).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Kolar et al, 1994), and experimentation with or abuse of alcohol and drugs (Biederman et al, 2000;King et al, 2003).…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…For example, compared with children of non-substance-abusing parents, children of substance-abusing parents are at a greater risk for parent and family conflicts, household financial difficulties, legal conflicts, and frequent moves (1)(2)(3). As a result of both genetic and environmental factors, parental substance abuse is associated with a number of negative consequences on children.…”
Section: Introductionmentioning
confidence: 96%
“…As a result of both genetic and environmental factors, parental substance abuse is associated with a number of negative consequences on children. For example, children of parents who abuse illicit drugs or alcohol have an increased likelihood for problematic behaviors, including decreased obedience, increased aggression, showing anger and irritability, fighting, teasing, increased involvement with deviant peers, and criminal activity (1,(3)(4)(5). These children are at risk for other social problems such as reduced social competence, increased withdrawal and detachment, and fear of new situations (4)(5)(6).…”
Section: Introductionmentioning
confidence: 96%
“…A prospective Dutch study found that only half of the children born to drug-using women were being cared for by either one or both parents at the end of a 5-year period, this figure despite an intensive social inter vention programme [21]. An American survey of women in a methadone programme reported that 15% of their children were in foster or adoptive care, with a high pro portion of them involved in criminal activity [22], How ever, a follow-up study of children born to 61 out of an original 84 women entered into a methadone programme reported that only 5 children were not in the care of their mother at 40 months [19].…”
Section: Non-specific Factorsmentioning
confidence: 99%